ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN DIVIDEN, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Rista Intan Permata Sari; Windiana Wahyu Ekaputri Suwondo; Yunia Six Putri; Wandira Regita Putri Cahyani; Sabhita Kamila Jasmine; Annisa Rahma Qur'aini (Jurnal Ilmu Akuntansi, 2024)
This research aims to investigate the impact of three main factors, namely managerial ownership, dividend policy, and debt policy, on firm value. Company value is vital parameter in evaluating the performance ans achievements of company in the market. To achieve a significant increase in company value, management must consider various internal and external factors that can influence their strategic decisions. In this study, researchers focused on these three factors, identifying their relationship to firm value. Manageril ownership is the main focus in assessing the extent to which managers have interest and incentives that are in line with the company's long-term goals. We also explore whether companies with consistent dividend policies tend to have a higher value in the market, as this can be considered an indicator a company's financial stability and health. By understanding the impact of managerial ownership, dividend policy, and debt policy, management  can take appropriate steps to achieve the company's long-term goals and increase shareholder confidence.